Kedudukan Bank Syariah dalam Sistem Perbankan di Indonesia - Made Warka; Erie Hariyanto (Institut Agama Islam Negeri Madura, 2016)
Banking is an important element in the development of a country. The function of the bank as that financial intermediary institution is crucial for the success or failure of community economic development in a country. Syariah Banking Regulation in Act No. 7 of the year 1992 as amended by Act No. 10 of the year 1998 was not specific and less accommodate of the operational characteristics of Syariah Banking so that was born the law of No. 21 of the Year 2008 concerning Syariah Banking. Syariah banking is banking that is based on Syariah principles. Also based to economic democracy and the precautionary principle, it should contain the values of justice, solidarity, equity and expediency.